A method for large-scale identification of protein arginine methylation. - Uhlmann, T; Geoghegan, V; Thomas, B; Ridlova, G; Trudgian, D; Acuto, O (2012)
The lack of methods for proteome-scale detection of arginine methylation restricts our knowledge of its relevance in physiological and pathological processes. Here we show that most tryptic peptides containing methylated arginine(s) are highly basic and hydrophilic. Consequently, they could be considerably enriched from total cell extracts by simple protocols using either one of strong cation exchange chromatography, isoelectric focusing, or hydrophilic interaction liquid chromatography, the latter being by far the most effective of all. These methods, coupled with heavy methyl-stable isotope labeling by amino acids in cell culture and mass spectrometry, enabled in T cells the identification of 249 arginine methylation sites in 131 proteins, including 190 new sites and 93 proteins not previously known to be arginine methylated. By extending considerably the number of known arginine methylation sites, our data reveal a novel proline-rich consensus motif and identify for the first time arginine methylation in proteins involved in cytoskeleton rearrangement at the immunological synapse and in endosomal trafficking.